Perspektif Hukum Pidana Dalam Polemik Pengajuan Sumpah Advokat: Telaah Putusan Mahkamah Konstitusi Nomor 35/PUU-XVII/2018 Atas Surat Ketua Mahkamah Agung RI Nomor 73/KMA/HK.01/IX/2015 - Faisal Faisal; Muhammad Rustamaji (Jurnal Hukum IUS QUIA IUSTUM, 2020)
The discussion regarding a single forum for advocates has been widely analyzed, but after the issuance of the Letter of the Chief Justice of the Supreme Court Number 73 / KMA / HK.01 / IX / 2015, the concept of a single container still leaves big questions. One of the questions in the realm of criminal law is whether the letter of the Chief Justice that allows an advocate organization other than PERADI to propose an Advocate oath to the High Court can be categorized as an act against criminal law and can be held criminally responsible at the same time? This type of normative legal research uses a conceptual approach and a case approach, especially with regard to judicial reviews. The collection of legal materials is carried out by studying the literature on primary legal materials and secondary legal materials. The results of the study concluded that the issuance of the Chief Justice of the Supreme Court No. 73/2015 which allowed advocacy organizations other than PERADI to propose an advocate's oath to the High Court could lead to acts against material criminal law. However, it is difficult to realize criminal liability for acts against criminal law due to the incomplete formulation, especially regarding the concept of contempt of court.